Carotid Blowout Syndrome in patients with head and neck cancer - Hassamo Ramos, Nadia (2015)
Introduction: Carotid blowout syndrome is a rare life threatening complication resulting from head and neck cancer treatment. The main predisposing factors are neck dissection, radiation therapy, local infection, tissue necrosis, vascular exposure and pharyngocutaneous fistula.Materials and Methods: The authors present a clinical case and bibliographic review contemplating the predisposing factors, clinical presentation, treatment and prognosis of this entity. The rupture of the carotid artery was observed on a patient with retromolar trigone carcinoma, exposed to radiation therapy and after surgical treatmentResults: Bleeding was controlled with carotid ligation. Other solutions for preservation of carotid lumen were considered inappropriate or unavailable. In spite of the expected high rate of cerebrovascular events, there were no neurological deficits observed in the postoperative period.Conclusion: Because of its severity, the carotid blowout syndrome must be considered in patients with head and neck cancer and serve as warning to the need for optimization of the oncologic treatment of these patients.